2014
DOI: 10.1002/app.41494
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, water absorption, and morphology of recycled polymer blend rice husk flour biocomposites

Abstract: Rice husk flour (RHF) biocomposites based on uncompatibilized and compatibilized recycled high density polyethylene/recycled polyethylene terephthalate (rHDPE/rPET) with ethylene‐glycidyl methacrylate (E‐GMA) copolymer were prepared through a two‐step extrusion and hot pressing with fiber loadings of 40, 60, and 80 wt %. Results showed that tensile and flexural properties increased. However, the elongation to break and impact strength decreased as the RHF loading increased. Compatibilizing polymer blend matric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 51 publications
6
45
0
1
Order By: Relevance
“…Vinylester/carbon specimens showed 8.57% degradation whereas isopolyester/carbon specimen showed reduction in ILSS of 10.5% at 60 0 C for duration of 196 days at hygrothermic conditions. The similar observations at higher duration and temperature had higher moisture absorption as reported by Chen et.al [16][17]. All the composite specimen analysed showed degradation in UTS, flexural strength and ILSS due to hygrothermic condition.…”
Section: Durability Studies At Hygrothermic Conditionsupporting
confidence: 76%
“…Vinylester/carbon specimens showed 8.57% degradation whereas isopolyester/carbon specimen showed reduction in ILSS of 10.5% at 60 0 C for duration of 196 days at hygrothermic conditions. The similar observations at higher duration and temperature had higher moisture absorption as reported by Chen et.al [16][17]. All the composite specimen analysed showed degradation in UTS, flexural strength and ILSS due to hygrothermic condition.…”
Section: Durability Studies At Hygrothermic Conditionsupporting
confidence: 76%
“…3. The relationship of water content with time appeared to conform to Fickian diffusion behavior, in that the water uptake increased rapidly during the initial stage and then gradually reached an equilibrium state (Chen et al 2015a). Table 2 lists the water uptake values of the rTPB/RH composites at 2 h, 24 h, and at maximum water uptake (Mm).…”
Section: Water Uptakementioning
confidence: 89%
“…According to ASTM D570-98 (Chen et al 2015a), the specimens were cut to a length of 76.2 mm, width of 25.4 mm, and height of 3.2 mm. Prior to immersion, the specimens were dried in an oven at 90 °C for 24 h to eliminate trapped moisture.…”
Section: Water Behaviourmentioning
confidence: 99%
“…According to Chen et al (2015b), rHDPE/rPET/E-GMA (70/25/5 w/w/w) was extruded via single screw extruder and then used as matrix for producing RH composites with the filler of 30 to 70 wt.% and 3% MAPE using twin screw extruder, the resultant composites showed a great enhancement in modulus properties and thermal stability. On the other hand, 40, 60, and 80 wt.% RH-filled composites (with 3% MAPE), based on treated and untreated rHDPE/rPET 75/25 matrix with 5% E-GMA, were extruded twice via twin screw extrusion; results indicated better mechanical results and dimensional stability for RH composites with treated matrix (Chen et al 2015a). Kaewkuk et al (2013) concluded that fiber treatment (alkali and heat treatment) and adding MAPP contributed to an enhancement the interfacial adhesion between the sisal fibre and the PP matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation